A Natural History of the Drag Queen Phenomenon. (15th May 2017) - Moncrieff, Michael; Lienard, Pierre
The drag queen cultural phenomenon has been described at length. However, the depiction of outlandish and hyperbolic womanhood and taunting and formidable behavior at the core of drag queens' public persona has still to be fully accounted for. We argue that these aspects of the drag queen's public appearance could best be understood in a signaling framework. Publicly donning extravagant woman's costumes attracts harassment and brings financial, mating, and opportunity costs, generating the conditions for the transmission of honest signals. By successfully withstanding those odds, drag queen impersonators signal strategic qualities to members of the gay community. Data collected among gay and straight participants support a costly signaling reading of the drag queen cultural phenomenon. Participants generally agree that successful drag queens typically incur costs, while gaining specific social benefits.